Span load modification via differential spoiler setting - Elsayed, Omer Ali; Asrar, Waqar; Omar, Ashraf Ali (2010)
The serious impact of the wing tips vortices of a large aircraft is well known. There are many examples of the damage caused to following aircraft caught up in the rotational wake shed from an upstream craft. Topology of the wake vortices downstream of the configuration will largely depends on the span wise load distribution. In order to measure the span load distribution on the wing, a wake integration technique based on the control volume approach was used. The half aircraft model was tested at high lift configuration as well as at various differential spoiler settings (DSS’s). Particle image velocimetry (PIV) was used to measure the cross flow velocities downstream the model at IIUM low speed wind tunnel. Results reveals a noticeable inboard shift of wing loading for deflected spoiler numbers 5 and 6 at 30o and 40o with jumps in the span load distribution as an indication for the strength of individual vortices (wing/flap vortices). Deflecting spoiler numbers 1 at 10o results in a mild outboard load shifting while deflected spoilers numbers 2,3,4,5and 6 at 5o results in a drop of lift distribution in the area of the deflected spoilers with no load shifting observed. Finally spoiler’s proves to be capable of altering the span load distribution with a reasonable pay off price in term of lift loss.